Baltileuctra gen. nov., a new genus of Leuctridae (Insecta: Plecoptera) in Baltic amber - Chen, Zhi-Teng (Zootaxa, 2018)
A new genus and species of the stonefly family Leuctridae, Baltileuctra foraminis gen. et sp. nov., is described and illustrated based on a well-preserved male specimen from the Eocene Baltic amber. The new genus possesses typical characters of Leuctridae but has diagnostic characters of the thoracic sclerites and terminalia. The relationship between the new genus and other leuctrids is briefly discussed.